Evaluation Of Equality Education Programme Package B In Pkbm Cahaya Ilmu Sub-District Pelabai, Lebong Regency - Sanusi Sanusi; Bambang Sahono (UNIB Press, 2019)
This study aims to evaluate the input, process and products of the Package B education equality program in PKBM Cahaya Ilmu Pelabai Subdistrict, Lebong Regency. This study uses an evaluative descripteve approach. Data collection is done by the method of observation, interviews, and documentation with the data source PKBM chairman, secretary, and tutors/educators. Proof of the validity of the data using triangulation techniques. Analysis of the data used is qualitative analysis with steps of data collection, data reduction, and conclusion drawing. The results of the research obtained in this study are: (1) Planning for the management of PKBM Cahaya Ilmu in the District of Pelabai, Lebong Regency is in a very good category, and observations on PKBM planning when seen are in accordance with existing standards and assessment guidelines. (2) Organizing the management of PKBM Cahaya Ilmu so far is well structured, this can be seen from the division of work management and the distribution of tutors' expertise. (3) The management implementation carried out at PKBM Cahaya Ilmu, goes according to the initial planning. (4) In the evaluation phase of the management of PKBM, it can be seen that the programs planned almost entirely can be said to be successful. The evaluation stage is also a good criterion, this can be seen from the various results obtained. But PKBM Cahaya Ilmu administrators need to correct some of the obstacles that occur and improve management in accordance with existing management standards.